EXPLORING THE ROLE OF ETHNIC IDENTITY IN FAMILY FUNCTIONING AMONG LOW‐INCOME PARENTS. Issue 5 (July 2015) - Hurwich‐Reiss, Eliana; Rienks, Shauna L.; Bianco, Hannah; Wadsworth, Martha E.; Markman, Howard J.
<x xml:space="preserve">Abstract</x> The majority of research on ethnic identity (EI) has highlighted its role in mitigating risks associated with racial discrimination; however, discrimination is only one of many stressors that ethnic minority individuals face. The current study examined the relationships between EI, emotional distress, and the parent–child relationship among ethnically diverse, low‐income parents. Results indicated significant associations between EI and emotional distress, and EI and the parent–child relationship for African American parents, but not for their Latino or European American counterparts. Furthermore, when examined separately by gender, stronger EI buffered the impact of economic hardship on emotional distress for African American fathers. The current study provides preliminary evidence that EI plays an important role in the lives of ethnically diverse parents who are facing economic hardship. Methods for embracing and fostering EI may be valuable to incorporate into therapeutic services and strength‐based intervention programming, especially when serving low‐income African American individuals.